STRATEGI PERTAHANAN HIDUP PARA NELAYAN DI DALAM MEMENUHI KEBUTUHAN HIDUP DI DESA MARIMBATI, KECAMATAN JAILOLO, KABUPATEN HALMAHERA BARAT, PROVINSI MALUKU UTARA - , Agustinus Setiawan Dwi Putranto Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
West Halmahera is actually a place and the potential for fisheries in eastern Indonesia where more coastal areas than inland, so that the greatest asset in this region are maritime affairs and fisheries. Villagers Marimbati almost all its inhabitants are fishermen, so they live and survive to make ends meet by relying as a fishermen. With increasing age and changing times that there are fishermen village coastal area Marimbati currently still remain in poverty and adversity, because they have limitations. The existence of that background, so the research conducted in the village Marimbati, to find out the real and actual problems encountered and experienced by coastal communities and fishermen to make efforts to form defense strategy fishermen living in overcoming the burden and problems of everyday life. Qualitative research was conducted using the approach of explorative and inductive data analysis. While the area used by the authors is the village of Marimbati district Jailolo, West Halmahera and its surroundings, which is the domicile of the fishermen as well as local fishing operations. From research conducted in the village Marimbati and the results obtained, then the strategies should be developed in villages Marimbati in terms of release of fishermen from poverty and adversity and to survive so well is: 1). Seek an increase in additional income (double incomes) for the community, 2). Improved Working Capital through cooperative efforts with the Bank